1987
DOI: 10.1152/ajprenal.1987.252.4.f670
|View full text |Cite
|
Sign up to set email alerts
|

Role of dipeptidyl peptidase IV in uptake of peptide nitrogen from beta-casomorphin in rabbit renal BBMV

Abstract: We examined the handling of radiolabeled beta-casomorphin, Tyr-Pro-[3H]Phe-Pro-Gly, by rabbit renal brush-border membrane vesicles (BBMV). The uptake of radiolabel into the vesicles was Na+-independent, but an inward-directed H+ gradient stimulated the uptake. The H+ gradient-dependent uptake was further accelerated by an interior-negative membrane potential, but inhibited in the presence of a protonophore. Treatment of the membrane vesicles with diisopropylfluorophosphate (DFP) greatly reduced the uptake of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The role of proline in dipeptides in their transport by peptide carriers has not been studied systematically. Reviewing the available data reveals that at least some Xaa‐Pro dipeptides are good substrates for both renal and intestinal type peptide transporters [12–15]. There is almost no information available regarding the effect of N‐terminal proline on the interaction of dipeptides with PEPT1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The role of proline in dipeptides in their transport by peptide carriers has not been studied systematically. Reviewing the available data reveals that at least some Xaa‐Pro dipeptides are good substrates for both renal and intestinal type peptide transporters [12–15]. There is almost no information available regarding the effect of N‐terminal proline on the interaction of dipeptides with PEPT1.…”
mentioning
confidence: 99%
“…Using brush‐border membrane vesicles from rabbit kidney, Miyamoto et al . [12] and Daniel et al . [14] found very low or undetectable affinities of Pro‐Gly and Pro‐Leu to the renal peptide transporter(s).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4). This system represents a barrier for natural (Hartrodt et al, 1982;Kreil et al, 1983;Miyamoto et al, 1987). DPP IV is known to be located in the brush-border membrane (Auricchio et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian systems, a number of different biological functions for DP-IV have been proposed, ranging from digestion (15) and amino acid salvage (16), because of its occurrence in the intestine and kidney, to an involvement, through proteolytic processing, in fibronectin-mediated cell movement and adhesion (17). Because of the high frequency of Gly-Pro sequences in collagen, Hopsu-Havu et al (18) suggested that this enzyme may play a role in collagen metabolism or catabolism.…”
mentioning
confidence: 99%